Relationship between foot pronation and quadriceps angle in the patients with patello femoral pain syndrome - T Tahmasebi; A Pourghasem (Vesnu Publications, 2008)
Introduction: Anterior Knee pain is common in people and athletes. One of the causes of this pain is structural problem in lower limbs such as quadriceps angle. Previous sudies show that Quadriceps angle of patients with Anterior knee pain is more than normal. Theoretically one of the most practical methods of decreasing the quadriceps angle is reducing the angle of sub-talar joint using insoles. Howerer, there is not a comprehensive study in this field. Materials and Methods: 18 patients with patellofemoral pain syndrome with increased pronation of sub-talar joint were screened. Then, their quadriceps and valgus angle were measured before and after using insoles. Paired t test used to analyse the data.before and offer applying the isales. Results: The results of the study showed a significant reduction in the mean value of the quadriceps angle at lower limbs after useing of insoles. Results also indicated a significant reduction in the mean value of valgus angle often using the in soles (p = 0.02) and (p = 0.04). Conclusion: Improving pronation of foot with functional orthetics can reduce both the angle of quadriceps and symptoms of patellofemoral pain syndrome. Key words: Quadriceps angle, functional foot orthetics, Biomechanics, Anterior knee pain , foot pronation.